Technical Education in Community Schools (TECS) Instructors’ Experience in their Retention: A Narrative Study - KC, Dev Krishna; Ghaju, Bikash (Journal of Training and Development, 2025)
This empirical paper aims to explore the Technical Education in Community Schools (TECS) instructors’ experiences in their retention. Three TECS instructors from the Kathmandu valley were purposively interviewed to extract their in-depth information. A narrative inquiry method was used to explore the research participants’ lived experiences about their teaching profession along with the various aspects of their retention. Herzberg's motivation-hygiene factor theory was adopted to overview the instructors’ retention at TECS. The study revealed that retention of the instructors is a matter of personal and professional concern. Due to low pay and no provision for job security, those instructors who were only involved in teaching were not satisfied. On the other hand, instructors were happy with their teaching professions as they were applying theoretical knowledge to their practical fields. A flexible working environment, a bureaucratic hurdles-free system, an updated curriculum with appropriate tools and equipment, and professional development opportunities are to be considered for the instructors’ retention at TECS. In a nutshell, TECS instructors’ retention is contextual and depends on working conditions, financial benefits, job security, and professional development opportunities.